Comprehensive analysis of mutational signatures reveals distinct patterns and molecular processes across 27 pediatric cancers - Thatikonda, Venu; Islam, S. M. Ashiqul; Autry, Robert J.; Jones, Barbara Christine; Gröbner, Susanne N.; Warsow, Gregor; Hutter, Barbara; Hübschmann, Daniel; Fröhling, Stefan; Kool, Marcel; Blattner-Johnson, Mirjam; Jones, David T. W.; et al. (Nature cancer, 2023)
Analysis of mutational signatures can reveal underlying molecular mechanisms of the processes that have imprinted the somatic mutations found in cancer genomes. Here, we analyze single base substitutions and small insertions and deletions in pediatric cancers encompassing 785 whole-genome sequenced tumors from 27 molecularly defined cancer subtypes. We identified only a small number of mutational signatures active in pediatric cancers, compared with previously analyzed adult cancers. Further, we report a significant difference in the proportion of pediatric tumors showing homologous recombination repair defect signatures compared with previous analyses. In pediatric leukemias, we identified an indel signature, not previously reported, characterized by long insertions in nonrepeat regions, affecting mainly intronic and intergenic regions, but also exons of known cancer genes. We provide a systematic overview of COSMIC v.3 mutational signatures active across pediatric cancers, which is highly relevant for understanding tumor biology and enabling future research in defining biomarkers of treatment response.